The effect of grain orientation on nanoindentation behavior of model austenitic alloy Fe-20Cr-25Ni. (1st October 2017) - Chen, Tianyi; Tan, Lizhen; Lu, Zizhe; Xu, Haixuan
Abstract: Instrumented nanoindentation was used to investigate the hardness, elastic modulus, and creep behavior of an austenitic Fe-20Cr-25Ni model alloy at room temperature, with the indented grain orientation being the variant. The samples indented close to the {111} surfaces exhibited the highest hardness and modulus. However, nanoindentation creep tests showed the greatest tendency for creep in the {111} indented samples, compared with the samples indented close to the {001} and {101} surfaces. Scanning electron microscopy and cross-sectional transmission electron microscopy revealed slip bands and dislocations in all samples. The slip band patterns on the indented surfaces were influenced by the grain orientations. Deformation twinning was observed only under the {001} indented surfaces. Microstructural analysis and molecular dynamics modeling correlated the anisotropic nanoindentation-creep behavior with the different dislocation substructures formed during indentation, which resulted from the dislocation reactions of certain active slip systems that are determined by the indented grain orientations. Graphical abstract: Image 1